Not quite burned out but crispy around the edges : inspiration, laughter, and encouragement for teachers - Draper, Sharon M. (Sharon Mills) (Portsmouth, NH : Heinemann, 2001)
Presents stories and essays designed to encourage teachers and remind them of why they chose their profession in the first place, touching on such topics and themes as reading, parents, special education, flexibility, and the big picture.
Professional
Professional
Keywords: High school teachers -- United States -- Anecdotes; Teaching; High school teachers -- Anecdotes; Teachers -- United States -- Anecdotes; Teaching